Changes of headspace volatile constituents of palm olein and selected oils after frying French fries - Omar, Muhammad Nor; Muhd Nor, Nor Nazuha; Idris, Nor Aini (Asian Network for Scientific Information, 2007)
Changes of aroma constituents of palm olein and selected oils after frying French fries have been studied. The aroma constituents of used oils were collected using a solid-phase microextraction (SPME) headspace technique with an absorbent of a divinylbenzene/carboxen (DVB/CAR) (50/30 microm) on polydimethylsiloxane (PDMS) fibre. The extracted volatiles were desorbed from the fibre in the injection port of the gas chromatograph at 250 degrees C and the aroma constituents were identified by GC-MS. Analytical data showed that volatile constituents of palm olein, soybean oil, corn oil and sunflower oil changed while frying continued from 2 to 40 h, respectively. In palm olein, the 2t,4t-decadienal content decreased from 14.7 to 5.5 microg g(-1) (40 h) whilst hexanal increased from 7.9 microg g(-1) (2 h) to 29.2 microg g(-1) (40 h), respectively. Similar result was also obtained from soybean oil after frying French fries. The 2t,4t-decadienal content decreased from 15.9 microg g(-1) (2 h) to 3.2 microg g(-1) after 40 h frying whilst hexanal increased from 10.2 microg g(-1) (2 h) to 34.2 microg g(-1) (40 h). Meanwhile, in corn oil, it was found that 2t,4t-decadienal decreased from 15.6 microg g(-1) (2 h) to 3.2 microg g(-1) (40 h) whilst hexanal increased from 11.3 microg g(-1) (2 h) to 33.8 microg g(-1) when frying time reached 40 h. In sunflower oil, it was found that 2t,4t-decadienal, decreased from 16.8 microg g(-1) (2 h) to 1.2 microg g(-1) (40 h) while hexanal increased from 9.5 microg g(-1) (2 h) to 32.4 microg g(-1) when frying time reached 40 h. It also showed that used oils exhibited off-odour characteristics due to the increasing amount ofhexanal while their freshness characteristics diminished due to the decreasing amount of 2t, 4t-decadienal.